Elaboração e avaliação de um material instrucional baseado na teoria da aprendizagem significativa : estudo de transformações de energia com o uso de uma maquete - Muniz, Rafael Oliari (2016)
This paper describes the application of an Instructional Material (IM) that covers concepts related to Energy Transformations. It was developed in compliance with the assumptions of the Theory of Meaningful Learning, from the perspective of Ausubel and Moreira, and the Theory of Motivation in Bzuneck perspective. The IM proposes the use of three teaching resources: the concept tests, an experiment and a model that addresses the main concepts used in IM. The investigation of the impacts of the use of Instructional Material was carried out following a design of experimental type in Stanley and Campbell perspective. Thus, the study was developed with an Experimental Class (EC), which received classes based on MI including the three proposed resources, and other Control Class (CC), where the intervention was made only by IM use. The choice is made randomly. EC has 14 students and CC with 8 students, both belonging to the State School of Elementary and Secondary Education Major Alfredo Pedro Rabaioli, located in Vitória, Espírito Santo state, Brazil. As data collection instrument were used a Pre and Post Test with 10 questions each, and 5 of the open type and 5 multiple-choice type, applied to both groups. A qualitative analysis from the answers to open questions of the tests was carried out. There was also a quantitative analysis from different criteria for open questions and multiple choice, generating a single score per test and averages to evaluate the individual performance of each class and in both tests. The analysis of the performances of the groups showed that there was an evolution of the EC from Pre to Post test more expressive the same comparison to CC, a statistically significant difference for the Wilcoxon statistical test. The results of this test, as well as qualitative analysis of student responses, present evidence that the IM and its proposed resources contributed to the motivation of students and the promotion of Meaningful Learning to the concept of Energy Transformations to the group of students of this School State.